Organic Acid Excretion in Penicillium ochrochloron Increases with Ambient pH - Vrabl, Pamela; Fuchs, Viktoria; Pichler, Barbara; Schinagl, Christoph W.; Burgstaller, Wolfgang (Frontiers in Microbiology, 2012)
Despite being of high biotechnological relevance, many aspects of organic acid excretion in filamentous fungi like the influence of ambient pH are still insufficiently understood. While the excretion of an individual organic acid may peak at a certain pH value, the few available studies investigating a broader range of organic acids indicate that total organic acid excretion rises with increasing external pH. We hypothesized that this phenomenon might be a general response of filamentous fungi to increased ambient pH. If this is the case, the observation should be widely independent of the organism, growth conditions or experimental design and might therefore be a crucial key point in understanding the function and mechanisms of organic acid excretion in filamentous fungi. In this study we explored this hypothesis using ammonium limited chemostat cultivations (pH 2-7), and ammonium or phosphate limited bioreactor batch cultivations (pH 5 and 7). Two strains of Penicillium ochrochloron were investigated differing in the spectrum of excreted organic acids. Confirming our hypothesis, the main result demonstrated that organic acid excretion in P. ochrochloron was enhanced at high external pH levels compared to low pH levels independent of the tested strain, nutrient limitation and cultivation method. We discuss these findings against the background of three hypotheses explaining organic acid excretion in filamentous fungi, i.e. overflow metabolism, charge balance and aggressive acidification hypothesis.